Seroprevalence for the tick-borne relapsing fever spirochete Borrelia turicatae among small and medium sized mammals of Texas. - Brittany A Armstrong; Alexander Kneubehl; Aparna Krishnavajhala; Hannah K Wilder; William Boyle; Edward Wozniak; Carson Phillips; Kristen Hollywood; Kristy O Murray; Taylor G Donaldson; Pete D Teel; Ken Waldrup; et al. (Public Library of Science (PLoS), 2018)
BACKGROUND:In low elevation arid regions throughout the southern United States, Borrelia turicatae is the principal agent of tick-borne relapsing fever. However, endemic foci and the vertebrate hosts involved in the ecology of B. turicatae remain undefined. Experimental infection studies suggest that small and medium sized mammals likely maintain B. turicatae in nature, while the tick vector is a long-lived reservoir. METHODOLOGY/PRINCIPAL FINDINGS:Serum samples from wild caught rodents, raccoons, and wild and domestic canids from 23 counties in Texas were screened for prior exposure to B. turicatae. Serological assays were performed using B. turicatae protein lysates and recombinant Borrelia immunogenic protein A (rBipA), a diagnostic protein that is unique to RF spirochetes and may be a species-specific antigen. CONCLUSIONS/SIGNIFICANCE:Serological responses to B. turicatae were detected from 24 coyotes, one gray fox, two raccoons, and one rodent from six counties in Texas. These studies indicate that wild canids and raccoons were exposed to B. turicatae and are likely involved in the pathogen's ecology. Additionally, more work should focus on evaluating rodent exposure to B. turicatae and the role of these small mammals in the pathogen's maintenance in nature.